1992
DOI: 10.1007/bf00046551
|View full text |Cite
|
Sign up to set email alerts
|

Constructional morphology of photoreceptor patterns in percomorph fish

Abstract: The frequently occurring photoreceptor patterns in fish are explained using functional and environmental demands in a geometric model. The shape of the double cone provides a number of constructional properties leading to a limited number of appropriate configurations. The probability of their occurrence is estimated from the degree to which the combination of properties of each eonfiguration meets specific environmental light conditions. A row pattern of merely double cones is especially suitable for vision i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…In general, as the optical properties of water cause to different wavelengths of light being absorbed to different degree, the fish need a various kind of cone cells to absorb such different wavelengths (Fernald, 1988;van der Meer, 1992). It is said that a single cone cell shows the highest absorption in the short wavelengths (green, blue), while double cone cells are the highest in the middle and long wavelength (red, orange) (Marc & Sperling, 1976;van der Meer, 1992). With such reports, it is possible that L. mediadiposalis enable feeding and survival in dim condition as a nocturnal fish.…”
Section: Discussionmentioning
confidence: 99%
“…In general, as the optical properties of water cause to different wavelengths of light being absorbed to different degree, the fish need a various kind of cone cells to absorb such different wavelengths (Fernald, 1988;van der Meer, 1992). It is said that a single cone cell shows the highest absorption in the short wavelengths (green, blue), while double cone cells are the highest in the middle and long wavelength (red, orange) (Marc & Sperling, 1976;van der Meer, 1992). With such reports, it is possible that L. mediadiposalis enable feeding and survival in dim condition as a nocturnal fish.…”
Section: Discussionmentioning
confidence: 99%
“…In general, middle and long-wave sensitivity are subserved by the double cone, while short-wave sensitivity is achieved by the single cone (Harosi and Hashimoto, 1983;Bowmaker and Kunz, 1987). The absorption maxima of the visual pigments of the non-identical double cones appears to be markedly smaller than those of the identical double cones in Cyprinids (Levin and MacNicol, 1979;van der Meer, 1992). As the identical double cone cells of Z. temmincki are totally developed compared to only the UM and LM of Z. platypus, we found that the eyes of Z. temmincki have a better resolution for detecting a moving prey in relative limpid water and swift current.…”
Section: Discussionmentioning
confidence: 99%
“…Tel cones occur occasionally in some species (Lyall, 1957;Engstrom, 1958Engstrom, , 1960Engstrom, , 1963Nicol, 1989;van der Meer, 1992;Nishiwaki et al, 1997;Cook and Chalupa, 2000;Carl, 2001;Lim et al, 2002;Mochizuki, 2002). And double cones are divided into equal double cones (twin cones) and unequal double cones by the cell size only.…”
mentioning
confidence: 99%
See 2 more Smart Citations